Meningkatkan Minat Belajar Siswa Dalam Pembelajaran PPKn Melalui Media Video di SMP Negeri 8 Bolaang Mongondow Utara - Ariani Olii; Zulaecha Ngiu; Asmun W. Wantu (Journal on Education, 2024)
This research discusses increasing students' interest in learning PPKN through video media at SMP N 8 Bolaang Mongondow Utara. Using qualitative research and a descriptive approach was carried out to obtain data that was appropriate to the problems existing in the school. These problems are a lack of motivation from teachers and a lack of facilities and infrastructure in schools, especially when using video-based media. This causes students' interest in learning PPKN to decrease and has an impact on their learning outcomes which are not optimal. The results of this research are that during the research process several obstacles were found, one of which was that students during the learning process were still noisy, coming in and out, and disturbing friends who were focused on studying. So the percentage obtained from the results of the analysis of the interest in learning questionnaire was 62.2%, but this is already included in the good category.